Caracterização fenotípica e molecular de Staphylococcus aureus isolados de mastite bovina - Salimena, Alessandra Pereira Sant’Anna (2016)
Mastitis is an inflammation of the mammary gland primarily caused by the invasion and multiplication of bacteria in the glandular parenchyma, and is considered of greater economic significance disease in world dairy farming. Staphylococcus aureus is a pathogen often associated with of mastitis dairy herds in around the world. Analysis of genetic diversity of S. aureus and the study of different strains have been seen as necessary steps for the effective control of the disease. Several virulence factors, such as resistance to phagocytosis recognition and binding to the lost extracellular matrix proteins, capsular polysaccharides and the ability to metabolize substrates present in the milk contribute to the genetic diversity of S. aureus and assist in the establishment of infection caused by the pathogen. Upon certain conditions, the microorganisms adhere, interact with various surfaces and initiate cell growth by forming biofilms. This study was conducted with the aim of detecting the presence of genes involved in capsular polysaccharide production and biofilm formation in S. aureus strains isolated from bovine mastitis samples located in three different regions of Brazil, as well as the production of polysaccharides and capsular biofilms, in vitro. The presence of the genes cap, icaAD and bap by PCR was evaluated. The detection and quantification of capsular polysaccharide production was performed using ELISA assays. The analysis of biofilm production was carried out in flat bottom sterile polystyrene microtiter plates with lid. All 159 isolates investigated harboured the cap gene being that 80% carried the cap5 gene and 20% carried the cap8 gene. Sixty-nine percent of the isolates have capsular polysaccharide (CP) in vitro, of these 58% are PC5 and PC8 11%. All isolates harboured the icaA and icaD genes, and 95.6% of the isolates carried the bap gene. Of the 159 isolates analyzed, 97.5% were biofilm producers. A significant association between the capsular genotype and phenotype and the amount of biofilm formation was detected. These results indicate a high pathogenicity potential among S. aureus isolated from bovine milk collected from three different regions of Brazil.